Echocardiographic evaluation in Dorper ovine fetuses: Applications and limitations - Cruz-Aleixo, Amanda Sarita [UNESP]; Lima, Mayra de Castro Ferreira [UNESP]; Albuquerque, Ana Luísa Holanda de [UNESP]; Teixeira, Raphael Tortorelli [UNESP]; Paula, Renata Alves de [UNESP]; Grandi, Marina Cecília; Ferreira, Danilo Otávio Laurenti; Tsunemi, Miriam Harumi [UNESP]; Chiacchio, Simone Biagio [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Wiley, 2021)
In this study we aim to show the application of ultrasound evaluation of the fetal heart in the ovine species, as well as its limitations in the field. Ten Dorper sheep, without any sedation, were evaluated starting from the second month of pregnancy through transabdominal ultrasound with an ultrasound device equipped with a convex transducer. Images of the fetal heart were obtained through maternal abdominal ultrasound by identifying the position of the fetus and conducting the following measurements: length and diameter of the heart, dimensions of the right and left ventricles and dimensions of the right and left atria. The measurements could only be conducted with acceptable precision starting from the third month of pregnancy. There was a significant difference only for left ventricle diameter, which was larger in the fifth month of pregnancy. The echocardiographic evaluation of the fetus enables monitoring the heart development identifying early fetal viability, assessing inadequate events that could put the pregnancy at risk, especially for production animals. For the experimental design of research employing production animals, it is important to consider, among other factors, the limitations of the evaluation on the field, such as restraining the animals, the stress caused by handling and environmental conditions, temperature, luminosity, facilities available and the qualifications of the team.
Keywords: development; fetal monitoring; heart; pregnancy; sheep; ultrasound